2015
DOI: 10.1111/jphp.12369
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Tween-20 and Tween-80 evaluated through different in-vitro tests

Abstract: Our findings raise concerns with regard to the indiscriminate use of Tween-20 and Tween-80 in clinical and laboratory testing, since they could influence the results that are assigned to the tested substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
(52 reference statements)
3
19
0
1
Order By: Relevance
“…T20 are considered hydrophilic in nature, hence the result of low DPPH scavenging activity was believed to be attributed by the hydrogen donation from the hydroxyl group (OH) present in the T20. This result was in accordance with a study by Pérez‐Rosés, Risco, Vila, Peñalver, and Cañigueral () that the limited DPPH values showed in Tween 20 and Tween 80 were due to the capability of hydrogen donation group. The slightly higher DPPH scavenging activity of β‐CD than T20 was attributed to the presence of more hydroxyl groups in cyclodextrin that able to donate more hydrogen atoms to reduce free radicals in the assay.…”
Section: Resultssupporting
confidence: 93%
“…T20 are considered hydrophilic in nature, hence the result of low DPPH scavenging activity was believed to be attributed by the hydrogen donation from the hydroxyl group (OH) present in the T20. This result was in accordance with a study by Pérez‐Rosés, Risco, Vila, Peñalver, and Cañigueral () that the limited DPPH values showed in Tween 20 and Tween 80 were due to the capability of hydrogen donation group. The slightly higher DPPH scavenging activity of β‐CD than T20 was attributed to the presence of more hydroxyl groups in cyclodextrin that able to donate more hydrogen atoms to reduce free radicals in the assay.…”
Section: Resultssupporting
confidence: 93%
“…In this case, both an increase in antioxidant activity and its inhibition has been observed. At the same time, in a study by Pérez-Rosés, it was confirmed that Tween 20 and Tween 80 did not show scavenging activity on DPPH radical and its presence in the medium does not distort the antioxidant activity analysis results [50]. In this regard, for a more accurate interpretation of the data on antioxidant activity obtained in this work, additional studies on the effect of Tween 80 not only on the yield of polyphenols, but also on its effect on the antioxidant properties of the recovered substances are required.…”
Section: Discussionmentioning
confidence: 77%
“…Tween 20 shares some structural similarity to Lipid A of Gram-negative bacteria, especially the short saturated fatty acids and has been implicated to affect the immune response and reactive oxygen species (ROS) production [ 34 ]. Tween 20 contains lauric acid that might be released and affect Tol-like receptors and induce NF-κB activation [ 56 , 57 ]. We demonstrate here that Tween does not play a role in the induction of IL-8 expression but that this is related to the MOI.…”
Section: Discussionmentioning
confidence: 99%